Karstic Microrefugia Host Functionally Specific Ant Assemblages - Bátori, Zoltán; Lőrinczi, Gábor; Tölgyesi, Csaba; Módra, Gábor; Juhász, Orsolya; Aguilon, Dianne Joy; Vojtkó, András; Valkó, Orsolya; Deák, Balázs; Erdős, László; Maák, István Elek (Frontiers in Ecology and Evolution, 2020)
Karst landscapes are among the topographically most complex systems with various microhabitats, where species can persist despite unfavourable macro-environmental changes. These microhabitats can also function as stepping stones during range shifts. Although the enclosed depressions (dolines, sinkholes or tiankengs) of karst landscapes may act as such safe havens, data on the functional diversity of their animal assemblages are scarce. Here, we investigate the functional diversity (i.e. certain functional groups and functional traits) of ant assemblages in dolines and study whether dolines surrounded by resource-poor environments (i.e. Fagus sylvatica forests) may function as safe havens for different kinds of ants. We found that dolines have the potential to maintain distinctive ant assemblages characterised by specific functional groups and traits that are rare in the surrounding habitats. Although continuous Fagus sylvatica cover in dolines had a detrimental impact on ant assemblages, grassland dolines surrounded by grasslands or Fagus sylvatica forests supported the presence of some specific functional groups and traits. These results suggest that conservation management needs to consider the influence of vegetation characteristics not only in dolines but also on the surrounding plateau. Moderate grazing and/or mowing would be desirable in order to prevent shrub encroachment into grasslands to ensure optimal vegetation structure for ants in the long run. Therefore, proper management and conservation of these safe havens may mitigate the rate of biodiversity loss under global warming. There is a need to explore a wide variety of taxonomic groups and taxon-specific traits in parallel with the quality of the surrounding habitats when evaluating current and potential microrefugia.